“I couldn’t play in it, but I loved it.”: Teachers’ Views on Participating in English Drama Performances - Puthut Ardianto (Journal of Foreign Language Teaching and Learning, 2016)
This study is an attempt to explore the teachers’ views on their participation in the English Drama Performance (EDP). Employing a qualitative approach, this study was conducted by selecting three English teachers from three different levels of education, who have been taking part in the EDP for a minimum of two performances. Data were collected through a one-on-one interview with each participant. The finding revealed that the teachers, at first were doubtful in participating in the EDP, however, after many rehearsals, they found enjoyment. In addition to their feelings, the teachers expressed their likes and dislikes in participating the EDP too. They also mentioned about the effect of their participation in the EDP towards their English skills. It turned out that by participating in the EDP, the teachers can express the English language function, enhance their pronunciation skill, practice communication skill, ease reading, and improve vocabulary. In addition to the effect on their English skills, their participation in the EDP contributes to the way they teach English to their students.